Low-Dose Fentanyl, Propofol, Midazolam, Ketamine and Lidocaine Combination vs. Regular Dose Propofol and Fentanyl Combination for Deep Sedation Induction; a Randomized Clinical Trial - Amini, Afshin; arhami, ali; Kariman, Hamid; Hatamabadi, Hamidreza; Memary, Elham; Salimi, Sohrab; Shokrzadeh, Shahram (Archives of Academic Emergency Medicine, 2018)
Introduction: Need for procedural sedation and analgesia (PSA) is felt in emergency department (ED) more and more each day. This study aimed to compare the effectiveness of low-dose fentanyl, propofol, midazolam, ketamine and lidocaine combination with regular dose of propofol and fentanyl combination for induction of deep sedation. Methods: In this single-blind clinical trial, candidate patients for sedation and analgesia aged more than 15 and less than 60 years old, with pain score ≥6 were allocated to one of the groups using block randomization and were compared regarding onset of action, recovery time, and probable side effects. Results: 125 patients with the mean age of 37.8 ± 14.3 years were randomly allocated to each group. 100% of the patients in group 1 (5 drugs) and 56.5% of the patients in group 2 (2 drugs) were deeply sedated in the 3rd minute after injection. The 2 groups were significantly different regarding onset of action (p = 0.440), recovery time (p = 0.018), and treatment failure (p < 0.001). Conclusion: Low-dose fentanyl, propofol, midazolam, ketamine and lidocaine combination was more successful in induction of deep sedation compared to regular dose of propofol and fentanyl combination. Recovery time was a little longer in this group and both groups were similar regarding drug side effects and effect on vital signs.